2022
DOI: 10.1002/adfm.202112685
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Hybrid Hydrogels Constructed via the Noncovalent Assembly for Biomimetic Tissue Scaffold

Abstract: Anisotropic structure is key for exploring the biomimetic functions of anisotropic hydrogels. However, the anisotropic hydrogel study should not be limited to its architecture design but must include the understanding and improvement of the internal interaction among their components. Herein, a noncovalent mediated assembly strategy is proposed to simultaneously improve the chitin chain mobility and enhance the interfacial interaction, for achieving anisotropic chitin/2D material (molybdenum disulfide and brus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 75 publications
0
43
0
Order By: Relevance
“…The anisotropy ratio (defined as the strength ratio between parallel and orthogonal directions) was 3.39, similar to literature reports. 80,81 Since Young's modulus of human skin was around 25 kPa, PACT hydrogel had skin-comparable Young's modulus (23.4 kPa), which should allow it to act as a wearable sensor. 35,82 The electrical conductivity of PACT hydrogel was also anisotropic (Fig.…”
Section: Anisotropic Mechanical and Conductive Propertiesmentioning
confidence: 99%
“…The anisotropy ratio (defined as the strength ratio between parallel and orthogonal directions) was 3.39, similar to literature reports. 80,81 Since Young's modulus of human skin was around 25 kPa, PACT hydrogel had skin-comparable Young's modulus (23.4 kPa), which should allow it to act as a wearable sensor. 35,82 The electrical conductivity of PACT hydrogel was also anisotropic (Fig.…”
Section: Anisotropic Mechanical and Conductive Propertiesmentioning
confidence: 99%
“…However, most hydrogels usually have an isotropic structure because they are made by homogeneous polymerization of monomers. 12,13 As a result, the isotropic hydrogels generally suffer from weak mechanical properties, severely restricting their application in flexible and wearable sensors. 14 On the other hand, the isotropic polymeric networks of hydrogels exhibit isotropic ion transport, which would greatly weaken the sensing performance of hydrogel-based electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a substantial number of problems between the electronics and the human body such as poor conformability, biological incompatibility, and lack of ductility are generated. , Hydrogels are a class of water-rich soft materials with tissue-like softness, satisfactory mechanical adaptability, high conductivity, and good biocompatibility. , These superior features make hydrogels the ideal candidates to prepare soft electronics. However, most hydrogels usually have an isotropic structure because they are made by homogeneous polymerization of monomers. , As a result, the isotropic hydrogels generally suffer from weak mechanical properties, severely restricting their application in flexible and wearable sensors . On the other hand, the isotropic polymeric networks of hydrogels exhibit isotropic ion transport, which would greatly weaken the sensing performance of hydrogel-based electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…18 An external field such as magnetic field 19 and electric field 20 can be applied to align the components in orderly row so as to obtain anisotropic hydrogel. Moreover, applying a force field to orientate the components for preparation of anisotropic hydrogel receives increasing attention, [21][22][23][24][25] due to the characteristics such as easily handling, processing and controlling. For example, Yang, Duan and coworkers 24 have stretched a chitin hydrogel to a certain strain, and then fixed the pre-stretched hydrogel to align the chitin chains to fabricate anisotropic hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, applying a force field to orientate the components for preparation of anisotropic hydrogel receives increasing attention, [21][22][23][24][25] due to the characteristics such as easily handling, processing and controlling. For example, Yang, Duan and coworkers 24 have stretched a chitin hydrogel to a certain strain, and then fixed the pre-stretched hydrogel to align the chitin chains to fabricate anisotropic hydrogels. They found that the pre-stretched hydrogel exhibited markedly improved Young's modulus and fracture toughness due to the aligned chitin nanofibrous structure, which meanwhile speeded up migration of cells to promote bone regeneration.…”
Section: Introductionmentioning
confidence: 99%